2021
DOI: 10.1177/20501579211052227
|View full text |Cite
|
Sign up to set email alerts
|

Oh, no, Pokémon GO! Media panic and fear of mobility in news coverage of an augmented reality phenomenon

Abstract: Media panics research is concerned with widespread social anxiety formed around a new technology or medium. This study adds to existing research by characterizing a new form of media panic around augmented reality applications, and specifically that which erupted concerning Pokémon GO, a popular augmented reality game. Based on a content analysis of items related to the game published in Israel's major print and online media in the period immediately following the game's launch, we classify the negative media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…They are most often men aged 18–30 with secondary education (more rarely higher), not in a relationship, living in cities with a population over 100,000—60.1% of players met these criteria. The results of our study are the same as the results of other studies, for example, the study of Laor et al (2021b) also showed that the most frequent players of urban games are adult males (67%, mean age 25.05 years).…”
Section: Discussionsupporting
confidence: 90%
“…They are most often men aged 18–30 with secondary education (more rarely higher), not in a relationship, living in cities with a population over 100,000—60.1% of players met these criteria. The results of our study are the same as the results of other studies, for example, the study of Laor et al (2021b) also showed that the most frequent players of urban games are adult males (67%, mean age 25.05 years).…”
Section: Discussionsupporting
confidence: 90%
“…Physical activity through AR videogames such as in Pokémon GO, may not only result in positivity due to the benefits of exercise, but also increase engagement in the gameplay experience because players are receiving sensory input both from their screens as well as their outdoor physical environments. Supporting this idea, existing work has linked physical activity to improved positivity and well-being both in games in general (Halbrook et al, 2019) and specifically in Pokémon GO (Bonus et al, 2018); although, we note there has been some skepticism regarding potential dangers associated with the physical mobility created by Pokémon GO (Laor et al 2021). There may be other ways in which Pokémon GO increases engagement with gameplay, leading to greater positivity.…”
Section: Unique Aspects Of Ar Games Relevant To Positivitymentioning
confidence: 65%
“…For instance, this counter angle can be seen in Valasek's (2021) critique of discourse around the psychology of user experience and well-being based on its checkered history. Likewise, other papers considered how mobile media can elicit moral panics and alarmism that goes before and/or beyond the scientific evidence (Laor et al, 2021;Rao & Lingam, 2020).…”
Section: Theme #3: Psychological Well-being and Alarmismmentioning
confidence: 99%